2019
DOI: 10.1186/s13034-019-0272-5
|View full text |Cite
|
Sign up to set email alerts
|

Favourable short-term course and outcome of pediatric anxiety spectrum disorders: a prospective study from India

Abstract: Background Although anxiety disorders are the most prevalent psychiatric disorders among children and adolescents, there is a paucity of research on the course and outcome of anxiety spectrum disorders in low and middle-income countries. Methods 60 children and adolescents aged 6–16 years with anxiety spectrum disorders attending the child and adolescent psychiatry department in a tertiary care center from India were included after taking written informed consent and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…In the current study, 29% of children with an anxiety disorder had school refusal and avoided school, reflecting significant impairment in academic functioning. These findings are similar to that of a latest study from National Institute of Mental Health and Neurosciences [21], which found that nearly one-third of the sample had school refusal. Although school refusal is not an anxiety disorder and may be motivated by many factors aside from anxiety, but when it occurs, anxiety is a common underlying element such as fear of the school work, separation anxiety, social fears, etc.…”
Section: Clinical Characteristicssupporting
confidence: 89%
“…In the current study, 29% of children with an anxiety disorder had school refusal and avoided school, reflecting significant impairment in academic functioning. These findings are similar to that of a latest study from National Institute of Mental Health and Neurosciences [21], which found that nearly one-third of the sample had school refusal. Although school refusal is not an anxiety disorder and may be motivated by many factors aside from anxiety, but when it occurs, anxiety is a common underlying element such as fear of the school work, separation anxiety, social fears, etc.…”
Section: Clinical Characteristicssupporting
confidence: 89%
“…Another recent study [44] has shown a favorable outcome in children and adolescents with anxiety spectrum disorders receiving treatment-as-usual in a tertiary care setting. The authors indicate a need for interventional research with a specific focus on universal preventive programs for anxiety spectrum disorders that are feasible for delivery in low and middle-income countries.…”
Section: Research On Cbt With Children and Adolescents In The Indian ...mentioning
confidence: 98%
“…For instance, in some studies, almost 30% children with anxiety disorders have been described to present with school refusal initially. 18, 19 Allen and colleagues have previously reported that mental health conditions impair the cognitive and emotional development of the child. 20 Often, this leads to difficulty coping with school and causes children to refuse to attend school.…”
Section: School Refusal: Key Conceptsmentioning
confidence: 99%